Efficient HEVC intra‐frame prediction using curved angular modes. Issue 21 (1st October 2018) - Fernandes, R.; Sanchez, G.; Cataldo, R.; Webber, T.; Marcon, C.
Abstract : Blending curved and straight lines on angular modes are proposed for intra‐frame prediction in high‐efficiency video coding (HEVC). All 33 angular modes in HEVC have received an offset‐based displacement calculation to each predicted sample, so that the resulting prediction block models image regions with curved textures. The proposal includes a negligible overhead in the syntax elements of the encoded bitstream (up to 2.56%) to transmit the curvature parameter along with the angular mode of a predicted block. Results demonstrate increased prediction accuracy and consequent reduction in residuals. There is a fair trade‐off between prediction accuracy and computational complexity even considering few curvature parameters. Further evaluations show an average reduction in Bjøntegaard delta rate of 3.19% for the HEVC test sequences.